A Case Report of Adrenal Pheochromocytoma (Faridpur Medical College Journal, 2011)
Pheochromocytoma is a rare catecholamine secreting tumour originating usually from adrenal medulla and produces signs and symptoms due excessive catecholamine secretion from tumour. A young female patient of 21 year age presented with paroxysmal attacks of hypertension causing palpitation, dizziness, blurring of vision and headache for last 06 months. Clinical suspicion of pheochromocytoma was confirmed by 24 hour urinary catecholamine level, transabdominal USG and CT scan of abdomen. After having two weeks of preoperative preparation with phenoxybenzamine and propanolol, open surgical removal of pheochromocytoma was done. Peroperative fluctuation of BP was well managed by IV fluid overload, intravenous phentolamine, intravenous esmolol and intravenous ephedrine. Postoperative recovery was uneventful and BP regains to normal range from 1st postoperative day. Pheochromocytoma is a rare cause of hypertension. If the diagnosis of pheochromocytoma is overlooked, the consequences could be disastrous, even fatal; however, if a pheochromocytoma is identified, it is potentially curable, as being one of the cause of surgically correctable hypertension. Key Words: Pheochromocytoma; catecholamine; hypertension; alpha blocker. DOI: 10.3329/fmcj.v6i1.7413 Faridpur Med. Coll. J. 2011;6(1): 55-58